2015
DOI: 10.14303/irjm.2015.132
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bio-aerosols in the outdoor air environment in Uyo Urban, Akwa Ibom state, Nigeria

Abstract: Outdoor bio-aerosols quality in Uyo urban was evaluated for their prevalence using settle plate (culturebased) method. Five (5)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Rainfall aid in the distribution of microbial particles from higher elevations to ground-level environments, while cloud acts as a cover to prevent the penetration of ultraviolet irradiation, which inactivates culturable microorganisms (Kang et al, 2015). However, this study is at variance with the reports of studies that opined that increased temperature and relative humidity of the e n v i r o n m e n t f a v o u r t h e g r o w t h o f microorganisms (Ren et al, 2001;Ambrose et al, 2015).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Rainfall aid in the distribution of microbial particles from higher elevations to ground-level environments, while cloud acts as a cover to prevent the penetration of ultraviolet irradiation, which inactivates culturable microorganisms (Kang et al, 2015). However, this study is at variance with the reports of studies that opined that increased temperature and relative humidity of the e n v i r o n m e n t f a v o u r t h e g r o w t h o f microorganisms (Ren et al, 2001;Ambrose et al, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…Several studies have reported species of the genus Proteus and Enterobacter in the air. These bacterial isolates have been associated with indoor and outdoor environments in previous studies (Wemedo et al, 2012;Ambrose et al, 2015;Al-Mayahi, 2017;Agwaranze et al, 2020). Proteus mirabilis is part of the normal flora of the human gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 77%